Menimbang Sentral Pelayanan: Misi dan Tanggung Jawab Gereja Menghadapi Skandal - Jabes Pasaribu Yabes (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
This research is a theological literature review of the complexity of the church's responsibilities as God's servants. It is revealed that contemporary Christianity reflects a potential falsehood between carrying out the duties and responsibilities of the church through reflecting on the character of Jesus Christ in ministry. This raises a dilemma regarding the central reflection of today's church ministry. The author uses a qualitative method of descriptive analysis in the form of text literature. In conclusion, the church today must reflect again on its duties and responsibilities in the essence of God's mission to save humans. So the center of ministry is a reflection of what Jesus did.